PENERAPAN MODEL PEMBELAJARAN YESUS DALAM MATIUS 7:24-29 TERHADAP HASIL BELAJAR SISWA DI SMPN 12 KOTA KUPANG - Marsi Bombongan Rantesalu; Hesti Arista Dara (EDULEAD: Journal of Christian Education and Leadership, 2020)
This research examines the learning model used by Jesus when preaching or teaching specifically found in Matthew 7: 24-29. There are several methods that Jesus uses in this section, namely: the lecture method, the method of storytelling and the method of parable. These methods were quite successful in Jesus' teaching as evidenced by the large number of followers who were amazed at him. In this study, we want to find out how the influence of the application of the method Jesus used on student learning outcomes. The method used in this study is a quantitative method with survey techniques. The research population was all of the ninth grade students in SMP Negeri 12 Kota Kupang with a total sample of 30 students. Data analysis was performed using statistical techniques with data analysis processes namely Descriptive Analysis, Test Requirements Analysis and Hypothesis Test. The results showed that the application of the Learning Method used by Jesus in Matthew 7: 24-29 had an effect on student learning outcomes at SMP Negeri 12 Kota Kupang by 40%.